Hedgehogs in the hall - Baglio, Ben M.; McNicholas, Shelagh (New York : Scholastic Inc., 2001)
Adhering to her parents' policy of not permiting wild animals to stay in their veterinary hospital, Mandy finds a "halfway house" for her rescued hedgehogs where they can rehabiltate before returning to the wild.
610
Accelerated Reader AR
Keywords: Hedgehogs -- Juvenile fiction; Veterinary medicine -- Juvenile Fiction; Animals -- Juvenile fiction